BASIC CONVERSATION TAHAP LANJUT SEBAGAI EMBRIO KAMPUNG INGGRIS DI KELURAHAN MRAGEN, KEC. MAOSPATI, MAGETAN (Eduscotech, 2023)
English proficiency is increasingly essential as a global lingua franca; however, formal education frequently emphasizes grammar-oriented instruction, causing anxiety and mental blocks that hinder students’ oral communication skills. Mragen Village, strategically located near Iswahjudi Air Base and a regional tourism route yet lacking an immersive English-speaking environment, presents strong potential for language-based community empowerment. This community service program aims to bridge the gap between linguistic theory and communicative performance by initiating the English Village embryo in Mragen through confidence-building and active conversational practice. The “Advanced Basic Conversation” program employs a progressive curriculum designed to elevate participants’ competence from basic utterances to more complex transactional dialogues. The implementation adopted Communicative Language Teaching (CLT) integrated with a Mental Block Reduction approach during an intensive two-day face-to-face training. Core activities included real-life scenario role-play sessions and a Micro-Community Simulation workshop, supported by a conducive facilitator-to-participant ratio to allow individualized coaching. The program outcomes showed a marked increase in participants’ speaking fluency, self-efficacy, and conversational readiness. In addition, the activity successfully produced digital promotional assets (vlogs and podcasts) for the branding of “Mragen English Village” and established a Language Awareness Group to serve as peer tutors. These outputs lay a strong foundation for developing a sustainable English-speaking ecosystem and future edutourism initiatives within the Maospati District.